2022
DOI: 10.3390/ijms23179708
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcription Factor PPAR-γ in the Pathogenesis of Psoriasis, Skin Cells, and Immune Cells

Abstract: The peroxisome proliferator-activated receptor PPAR-γ is one of three PPAR nuclear receptors that act as ligand-activated transcription factors. In immune cells, the skin, and other organs, PPAR-γ regulates lipid, glucose, and amino acid metabolism. The receptor translates nutritional, pharmacological, and metabolic stimuli into the changes in gene expression. The activation of PPAR-γ promotes cell differentiation, reduces the proliferation rate, and modulates the immune response. In the skin, PPARs also contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 253 publications
(328 reference statements)
1
5
0
Order By: Relevance
“…Recently, with the emerging importance of PPARγ in psoriasis, ongoing studies have focused on restoring reduced PPAR-γ levels. 66 In the present study, AuNR-DX and laser combination therapy restored PPAR-γ more effectively than AuNR-DX alone in psoriasis skin (Figure 7b, bottom), mouse skin (Figure 7c,d), keratinocytes (Figure 7e,f), and reduced skin thickness and PASI scores (Figure 7g,h).…”
Section: Enhanced Pharmacological Effects Of Aunr-dx and Nir Laser Co...supporting
confidence: 52%
See 1 more Smart Citation
“…Recently, with the emerging importance of PPARγ in psoriasis, ongoing studies have focused on restoring reduced PPAR-γ levels. 66 In the present study, AuNR-DX and laser combination therapy restored PPAR-γ more effectively than AuNR-DX alone in psoriasis skin (Figure 7b, bottom), mouse skin (Figure 7c,d), keratinocytes (Figure 7e,f), and reduced skin thickness and PASI scores (Figure 7g,h).…”
Section: Enhanced Pharmacological Effects Of Aunr-dx and Nir Laser Co...supporting
confidence: 52%
“…PPAR-γ can be activated by photothermal therapy and is involved in regulating epidermal hyperproliferation and abnormal keratinocyte differentiation, rendering it a potential therapeutic target for psoriasis treatment. Recently, with the emerging importance of PPAR-γ in psoriasis, ongoing studies have focused on restoring reduced PPAR-γ levels . In the present study, AuNR-DX and laser combination therapy restored PPAR-γ more effectively than AuNR-DX alone in psoriasis skin (Figure b, bottom), mouse skin (Figure c,d), keratinocytes (Figure e,f), and reduced skin thickness and PASI scores (Figure g,h).…”
Section: Resultsmentioning
confidence: 99%
“…Propagated uterine Mø expressed CD36, a scavenger receptor with affinity to oxidized low-density lipoproteins [ 56 ], as well as Lxra and Pparg , transcription factors regulating lipid metabolism [ 57 , 58 ]. StAR is a cholesterol transport protein regulating steroidogenesis in the rate-limiting initial step [ 59 ], and thus uterine Mø may be deeply implicated in cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathophysiology of psoriasis bears some similarities with AD, including obesity, microbial dysbiosis and Th17-mediated inflammation ( 89 ). Clinical studies identified anti-psoriatic effects of TZDs ( 90 ), suggesting these medications may help in AD. Nevertheless, the skin microbiome is distinct in psoriasis and characterized by Corynebacteria spp.…”
Section: Atopic Dermatitismentioning
confidence: 99%